Analisis Bibliometrik Penelitian Tentang Studi Islam Pada Perpustakaan di Database Web of Science (2004–2024) - Adi Nugroho (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Studies related to Islam have received significant global attention. This is because Islam encompasses not only religion but also economics, finance, and community culture. Libraries' contributions to Islamic studies research are essential as providers of public information and literacy. This study aims to observe the popularity of Islamic studies research on the Web of Science (SCI). This study uses secondary data downloaded from the SCI website. This study analyzed 174 Web of Science articles (2004–2024) using bibliometrics using R Studio Biblioshiny. The samples were downloaded as CSV files and analyzed using R Studio software to analyze frequently used words in titles and abstracts, the number of citations, annual keyword trends, and the most cited affiliations. Furthermore, the dominant keywords (Islamic, libraries, Malaysia, library, study) were found, with Malaysia and Pakistan as the main contributors. However, international collaboration remained low (14.37%). The topic evolution shifted from infrastructure themes (academic libraries) to substantive Islamic issues (Islam, waqf, finance). Iran, Saudi Arabia, and Pakistan are the most cited affiliates, highlighting regional dominance as well as the research gap on the role of libraries in Islamic socio-economic literacy.